Ontology instantiations for software engineering knowledge management - Wongthongtham, Pornpit; Chang, Elizabeth (IEEE, 2007)
In this paper, we explore the development of systems for software engineering knowledge management. Software engineering knowledge is represented in the software engineering ontology whose instantiations, which are undergoing evolution, need a good management system. Software engineering ontology instantiations signify project information which is shared and has evolved to reflect project development, changes in the software requirements or in the design process, to incorporate additional functionality to systems or to allow incremental improvement, etc. In a large volume of updated project information, systematic management is of importance.